The Effectiveness of Papaya Leaf Extract (Carica papayaL.) Against Aphidsspin Tomato (Solanum lycopersicum) Plantation in the Natural Fence Area of South Sumatra - Riri Novita Sunarti (Biota, 2019)
AbstractPagaralam is one of the tomato suppliers for the South Sumatera region. Tomatoes are often attacked by pests such as aphids. Aphids fleas (Aphid sp.) are one of the main pests besides that aphids are important vectors that can transmit viral disease. The use of chemical insecticides can damage agricultural land for the use of vegetable insecticide alternatives. Alkoloid, Flavoid, Saponin, and Tanin contained in papaya leaves (Carica papaya) can be used as a plant aphid insecticide. The sample in this study was a 2 month old tomato plant with 20 aphids in each tree. Treatment was given to 5 treatment with 5 replications. This treatment by giving different concentrations of papaya leaf solution in the crop of 0%, 15%, 30%, 45%, and 60%. To determine the effectiveness of papaya leaf solution (Carica papaya) as a vegetable insecticide aphid done spraying as much as 100 ml once spray with contact time observation 12 hours and 48 hours. The results showed that the application of papaya leaf juice was effective in killing aphids, so that high concentrations that gave greater precentage of aphids deaths ranged from 24 hours showed F count > and F table and received at level 1% means that papaya leaf juice was very influential on aphids death. Then the results of cofactor coefficient (KK) 24 hours and 48 hours were 10% and 4%, before using The Smallest Significant Difference Test (BNT) to see the effect of each concentration. BNT Test pre view, each concentration was very significant which had a different effect on the death of ticks to analyze probit LC50 to determine the effective concentration of killing 50% of the samples at 39,81%. This is related to every usage given such as concentration and monitoring time. Keywords: Papaya Leaf (Carica papaya); Papaya Leaf Solution Concentration; Fleas (Aphid sp.)